Special endurance exercises and their effect on the level of lactate ion and some elements of special physical fitness and the achievement of 800 m running for people with disabilities, category CP38 (Damu Journal of Sport Sciences, 2024)
The category of people with disabilities ((CP38) is one of the categories that suffer from a defect that affects the brain and thus the occurrence of hemiplegia, whether congenital or as a result of a specific event (Cerebral Palsy), i.e. hemiplegia from half the brain to the soles of the foot. This paralysis makes parts of the body uncontrolled in terms of movement as well as the extension and flexion of the working muscles and the assistance that the body needs in performance and for all parts of the body and causes loss of focus, especially in the affected limbs that suffer from paralysis, and thus affects the achievement of the competitors and the failure to achieve the goal, as the importance of the research lies in the special endurance exercises that have a major role in the effect of the level of lactate ion and some special physical elements for 800 m competitors Running for people with disabilities category CP38. The research aims to the following:1-Preparing special endurance exercises on the effect of lactate concentration and some special physical fitness elements (strength endurance - speed endurance) for 800m running event competitors for people with disabilities category (CP38) Identifying the effect of special endurance exercises and the level of achievementThe researcher concluded the following:1-Special endurance exercises developed the lactate level for 800m running competitors for people with disabilities category CP38.2-Special endurance exercises developed some special physical fitness elements for 800m running competitors for people with disabilities category CP38.